FENOMENA CHILDFREE DI KALANGAN PERNIKAHAN MASA KINI (Tinjauan Hukum Gereja terhadap Kelahiran dan Kesejahteraan Anak) - Leonard Brahmandika (Aggiornamento, 2022)
Marriage is an agreement between husband and wife in a relationship. Marriage is one and is inseparable. Marriage in the Catholic Church is one of the sacraments of mission other than the sacrament of ordination. However, there are many problems and conflicts that occur in marriage. One example of the problem is the rejection of birth, education and child welfare. This phenomenon is referred to as childfree phenomenon. The focus of this study is to examine the phenomenon of childfree that occurs among today's marriages. This phenomenon is already run by several people including artists and public figures. The methodology used in this phenomenon is a case study. The authors collect and examine cases related to this phenomenon. The goal of the study was to find the cause of married couples who chose not to have children. The study found that married couples who choose not to have children because they want to focus on their marital relationships and careers.